Market entry strategies in a high-tech successive generations market: a case study of three semiconductor firms with different entry modes. Issue 11 (30th March 2020) - Park, Changhyun
Abstract : Purpose: The purpose of this study is to explore market entry strategies in a high-tech successive generations (HTSGs) market, by investigating entry mode via entry timing and path differentiation and the performance outcomes of entry mode. Design/methodology/approach: The methodology of building a theory from a longitudinal case study is adopted by using useful cases in a HTSGs market after constructing an integrated research framework to explore market entry mode. Different entry modes were investigated by studying entry timing and migration path of three firms' case in logic semiconductor market. In addition, performance outcomes of different entry modes were measured and correlated with each other. Findings: The results identified three major entry modes suitable for a HTSGs market. The three firms differentiated their entry modes by exploiting different entry timings from the earliest to the last and different migration paths including switching, leapfrogging and new entrance path to enter a market. First mover advantage also exists in a HTSGs market, and it was found uniquely that the financial performance denoted by entry mode outcomes was correlated with technological knowledge. Research limitations/implications: This study extends the theory of extant entry strategy from general consumer or industrial market to HTSGs market, in which intense competition exits and technological innovation is important. Moreover, this study verified that the causality between early entry and positive performance was also effective in HTSGs market with a shorter duration of early entry advantage. Practical implications: This study has managerial implications for firms to establish market entry strategy in HTSGs market and other markets. To become a product leader, a fast follower or a late follower, firms can differentiate their entry mode by adjusting the entry timing and migration path in the context of market and technology. Originality/value: This study examined market entry strategies suitable for HTSGs market based on its unique characteristics and extended relevant theory into HTSGs market. Further, an integrated research framework, which explores the market entry mode, was constructed to facilitate further exploration of entry mode into other markets.